Transformation of Islamic Law in Responding to the Challenges of Modernity by Integrating Classical Fiqh and Contemporary Fiqh - Suryantoro, Dwi Dasa (al-Rasῑkh: Jurnal Hukum Islam, 2025)
Islamic law, as a legal system rooted in religious traditions and values, faces great challenges in adapting to the dynamics of modern life. Contemporary fiqh emerged as a solution to this challenge, by offering a more flexible and responsive interpretation to social, political, and technological changes. This article aims to analyze the transformation of Islamic law through contemporary fiqh and the renewal of ushul fiqh to accommodate contemporary issues, such as women's rights, religious pluralism, and individual freedom. It is important to remember that contemporary fiqh does not replace classical fiqh, but rather develops a more flexible interpretation of law, while respecting the basic principles contained in classical fiqh. The research method used is a descriptive qualitative approach with thematic analysis of relevant literature. The results of the study show that contemporary fiqh can serve as a bridge between classical fiqh and the needs of modern times, while maintaining the core values of Islamic law. The contribution of this research lies in the offer of a conceptual framework that strengthens the relevance of fiqh in answering the challenges of modernity in an applicative and contextual manner.